The Role of Correctional Officers in the Development of Inmates at Class IIA Cibinong Correctional Facility - Al Fauji, Muhamad; Hartini, Sri; Purwaningsih, Prihatini (Universitas Ibn Khaldun Bogor, 2025)
The role of correctional officers is integral in fostering inmate development within correctional facilities, with the ultimate goal of transforming inmates into law-abiding and productive members of society. This study employs a qualitative descriptive method with a juridical-empirical approach. Data were collected through interviews with correctional officers, facility leadership, and inmates, as well as direct field observations. The findings reveal that correctional officers fulfill three primary roles: as facilitators, communicators, and motivators. Their facilitation role involves providing skill-building and character development programs. As communicators, they act as intermediaries between inmates, the correctional institution, and society. Their motivational role includes offering moral encouragement to inmates to participate actively in development programs. However, officers face several challenges, such as limited human resources, inadequate facilities, and societal stigma against inmates, which hinder social reintegration efforts. Enhancing the capacity of correctional officers and fostering multi-stakeholder support, including from the government and community, is critical to creating a more effective and sustainable inmate development system.